Gaming and extremism: the radicalization of digital playgrounds - Schlegel, Linda; Kowert, Rachel (Routledge, 2024)
"Charting the increase in the use of games for the dissemination of extremist propaganda, radicalization, recruitment, and mobilization, this book examines the 'gamification of extremism.' Editors Linda Schlegel and Rachel Kowert bring together a range of insights from world-leading experts in the field to provide the first comprehensive overview of gaming and extremism. The potential nexus between gaming and extremism has become a key area of concern for researchers, policymakers, and practitioners seeking to prevent and counter radicalization and this book explores key trends and debates, future directions, and potential prevention efforts. This includes the exploration of how games and game adjacent spaces, such as Discord, Twitch, Steam, and DLive, are being leveraged by extremists for the purposes of radicalization, recruitment, and mobilization. Additionally, the book presents the latest counter-terrorism techniques and promising preventing / countering violent extremism (P/CVE) measures currently being utilized in the gaming sphere and explores the ongoing challenges, controversies, and current gaps in knowledge in the field. This text will be of interest to students and scholars of gaming and gaming culture, as well as an essential resource for practitioners working in prevention and counter-extremism, professionals working at gaming-related tech companies, and policymakers"--